Analisis Perbedaan Gerakan Takbir dalam Sholat Menurut 4 Mazhab - Fitriyyah, Rofii’atul (AKADEMIK: Jurnal Mahasiswa Humanis, 2025)
Prayer is an obligatory act of worship for Muslims which is a pillar of religion and one of the second pillars of Islam, which is carried out five times a day. One of the important movements in prayer is takbir, which is done at the beginning of worship. There are differences in the practice of takbir movements between the four major schools of thought, namely Hanafi, Maliki, Syafi'i, and Hanbali. The Syafi'i School recommends the position of the hands above the navel below the chest, while the Maliki School believes that the hands should be straightened (irsal), without the need to cross your arms. The Hanafi and Hanbali schools agree that the hands should be crossed with a position below the navel. This research aims to analyze the differences in takbir movements in prayer according to the four schools of thought. The method used in this research is library research with a qualitative approach, which analyzes literature related to fiqh and hadith from each school of thought. The research results show that differences in the takbir movement are rooted in differences in interpretation of existing hadiths. In conclusion, even though there are differences in practice, all of these views are valid and acceptable within the framework of Islamic teachings, so that Muslims can choose to follow the school of thought they believe in.